Nutritional and management strategies to improve beef and pork production efficiency - Dahmer, Payton Lane (Kansas State University, 2023)
The weaning transition is a crucial time in swine production, as piglets experience physiological and nutritional changes as well as exposure to potential pathogens such as enterotoxigenic Escherichia coli (ETEC). Historically, nutritional interventions such as supplementation of pharmacological zinc oxide (ZnO) have been used to manage post-weaning diarrhea caused by ETEC. However, there is consumer and regulatory pressure to limit these practices, thus, alternative management or nutritional strategies are being investigated. Two experiments were conducted to evaluate dietary acidifiers and microencapsulated zinc oxide (ZnO) on weanling pig health and performance. In the first experiment, a total of 350 pigs (DNA 400 x 200; initially, 5.7 ± 0.06 kg BW) were used in a 42-d study with 5 pigs per pen and 14 replicate pens per treatment. At weaning, pigs were allotted to pens in a completely randomized design and pens of pigs were randomly assigned to one of five dietary treatments consisting of a negative and positive control (150 vs. 3,000 ppm Zn from ZnO) or three different types of dietary acidifiers. Overall, pigs fed a 1.0% blend of formic acid and glycerol monolaurate had reduced (P < 0.0001) ADG compared to those fed control diets. Fecal DM was evaluated from d 7 to d 28 and there was a treatment x day interaction (P = 0.04). In the second experiment, a total of 300 pigs (DNA 200 x 400; initially 6.0 ± 0.08 kg BW) were used in a 42-d study with 5 pigs per pen and 12 pens per treatment. At weaning, pigs were randomly allocated to pens and pens randomly allotted to dietary treatments. Dietary treatments consisted of a negative control (110 ppm Zn from ZnO) or two levels of ZnO (400 vs. 3,000 ppm Zn from ZnO) or two levels of microencapsulated ZnO (400 vs. 3,000 ppm Zn from microencapsulated ZnO). There was no evidence of differences in ADG, ADFI, or G:F for the entire treatment period (d 0 to d 28; P > 0.05). During the common phase 3 (d 28 to 42) pigs fed the negative control, High-MZnO, or Low-MZnO had improved (P < 0.0001) ADG compared to pigs fed High- or Low-ZnO. A significant treatment x day interaction (P = 0.04) was observed for fecal Zn concentrations, where the level of Zn excreted in the feces was dependent on the sampling day in pigs fed a low level of ZnO or low level of microencapsulated ZnO, while excretion of Zn did not differ between d 10 and 28 in pigs fed a negative control, high level of ZnO, or high level of microencapsulated ZnO. In a third experiment, 80 crossbred, high-risk heifers (initially 250 ± 4.2 kg BW), were transported from an Oklahoma City, Oklahoma sale barn to the Kansas State University Beef Cattle Research Center. Cattle were unloaded and randomly placed into one of four receiving pens. Each pen was randomly assigned to one of four rest-times before processing ranging from 0 to 48 hours. Processing time did not impact (P > 0.05) heifer BW or ADG. A significant processing time x day interaction (P < 0.0001) was observed for the prevalence of fecal parasites, where the percentage of positive samples was significantly lower 14-d after anthelmintic treatment, regardless of the processing time. While animal-based research is critical for us to make science-based decisions about animal management, we also must make science-based decisions about student education. Our undergraduate research (UGR) program has grown in recent years, but it was necessary to evaluate the learning outcomes of students engaged in these experiences. To do this,167 undergraduate students in the Department of Animal Sciences and Industry at Kansas State University completed an anonymous, retrospective post-then-pre-test to assess their perceptions of how the UGR experience impacted the development of professional skills and research competence. Students participating in either an independent (student paired with faculty member in 1:1 ratio) or course based (approximately 20 students paired with 1 faculty member) UGR experience completed the assessment at the end of the academic semester following conclusion of the UGR project. A comparison group of students not completing any form of UGR were also surveyed. Students completing a course-based UGR experience reported significant increases (P < 0.02) in professional skill development compared to students not completing UGR, while those who participated in an independent UGR experience were intermediate. Students participating in course based UGR reported increased (P < 0.0001) gains across all skill areas related to research methods compared to those not completing UGR. Based on student responses, completion of an UGR experience has positive implications for professional skill development and comprehension of how science is practiced.
Keywords: Nursery pig; Growth performance; Feedyard; Undergraduate research